‘Everyday Life’ in the Works of Maria Bogucka - Wiślicz, Tomasz (Acta Poloniae Historica, 2023)
The article discusses the use of the category of ‘everyday life’ in historical works by Maria Bogucka as well as her theoretical contributions on the subject. Her pioneering role in adapting the mode of popular writing advanced by the French cycle Histoire de la vie quotidienne to Polish historiography in the 1960s established a high-quality standard on Polish scholars by combining original research into economic and social history with references to the history of material culture and mentalities. A quarter of a century after the publication of her exemplary study entitled Życie codzienne w Gdańsku: wiek XVI–XVII [Everyday Life in Gdańsk: Sixteenth and Seventeenth Centuries, 1967], Bogucka involved herself in contemporary debates within the international community of historians over the German Alltagsgeschichte, perceiving it as a methodological framework for innovative research and an opportunity to expand the theoretical side of cultural history. Though she would not produce another ‘history of everyday life’ – in a refreshed perspective and with more robust theoretical foundations – her studies into old Polish customs betray an inspiration with the German research current of Alltagsgeschichte, which blossomed in the early 1990s.